Perbedaan Motivasi Kerja dan kepuasan kerja pegawai puskesmas Blud dan Non Blud Kabupaten Semarang - Aswindar Adhi Gumilang; Tri Pitara Mahanggoro; Qurrotul Aini (Universitas Ngudi Waluyo, 2019)
Every person has the right to obtain optimal health services. Public demans for profesinalism jn health sevices, transparent and accountable financial management make some health centers in Semarang district change their status to BLUD health centers. The implementation of BLUD and non-BLUD health centers requires resources that can work well in order to meet community expectations.this study aims to determine differences of work motivation and job satisfaction between BLUD and non-BLUD health center employees. Tjis research is deskriptive komparative study with quantitative approach. Sampel of this study carried out withSlovin formula and obtained as many as 138 samples. The variables studied were work motivation and job satisfaction. Data analysis was performed using the Oneway Anova test. The results showed that there were significant differences in work motivation between BLUD puskesmas employees and non BLUD health center employees, and there were significant differences in job satisfaction between BLUD puskesmas employees and non BLUD health center employees.